Improving the Process of Expressing and Sharing Higher Education Students’ Opinions Through EduTech Tools - Nafisa Ruzikulovna Khujamkulova (Researchparks Publishing, 2026)
In the modern education system, increasing students’ active participation and developing their cognitive abilities are considered among the most pressing issues. In traditional classroom settings, opportunities for students to freely express their opinions are limited, which restricts the full manifestation of their creative and critical thinking abilities. The relevance of this study arises from the need to improve the process of eliciting and effectively utilizing students’ ideas through the use of interactive and digital tools in higher education institutions. The main purpose of this research is to experimentally investigate the effectiveness of expressing and sharing students’ opinions using the interactive platform Padlet Sandbox. A mixed-methods methodology was employed in the study, combining quantitative and qualitative analyses. A total of 60 third-year students from the Samarkand State Pedagogical Institute participated in the research and were randomly assigned to experimental and control groups. In the experimental group, classes were organized using the Padlet Sandbox platform for 12 weeks, while traditional teaching methods were applied in the control group. Data were collected through questionnaires, observations, in-depth interviews, and content analysis. Statistical analyses (t-test, ANOVA, and regression analysis) were conducted using SPSS 26. The results demonstrated that the level of opinion expression among students who used the Padlet Sandbox platform was 34% higher than that of the control group (p < 0.01). In addition, collaborative skills among students in the experimental group increased by 28%, while creative thinking abilities improved by 41%. The platform also ensured anonymity among students, reduced hesitation, and increased the level of active idea exchange. The findings of the study theoretically expand the possibilities of applying constructivism and connectivism educational theories in practice. From a practical perspective, the results suggest that higher education institutions can organize learning processes using interactive platforms, value students’ opinions, and promote their cognitive development through appropriate methodological recommendations. The limitations of the study include the selected sample size and duration. Future research is recommended to investigate the effectiveness of this platform in different cultural and linguistic contexts.